Concours scolaires Ar Falz entre 1955 et 1965, un outil pédagogique pour pallier les insuffisances de la loi Deixonne ? - Maryvonne Berthou (Lengas)
Were the school competitions "Ar Falz" between 1955 and 1965 an educational means of compensating for the inadequacy of Deixonne 's law.Deixonne's law, passed in 1951, stipulates that any teacher  who makes the request  will be allowed to devote an hour of activities each week to the teaching of Breton.The leaders of the association "Ar Falz", including Armand Keravel, took strong action to be allowed to teach Breton in school while respecting this legislative framework and so they organised school competitions from the year 1952.Firstly we will  briefly describe those school competitions.Secondly we will present and analyse some of those writings.We have been able to meet some former pupils; these interviews permit us to establish the conditions in which those competitions took place and the relationship those children have maintained in relation to the Breton language. Several issues will emerge and will lead us to ask this question: has not the beginning of Breton teaching in primary schools fallen twenty years behind in regard to the sociolinguistic situation of Basse Bretagne.